NORAD TLE Conversion from Osculating Orbital Element - Byoung-Sun Lee (Journal of Astronomy and Space Sciences, 2002)
The NORAD type Two Line Element (TLE) was obtained from the osculating orbital elements by an iterative approximation procedure. The mathematical model was presented and computer program was developed for the conversion. The osculating orbital elements of the KOMPSAT-1 were converted into the NORAD TLE. Then the effect of the SGP4 atmospheric drag coefficient (B*) was analyzed by comparison of the orbit propagation results with different B* values.